A Retrospective Study of Factors Affecting Pathway and Time to Diagnosis, Time to Treatment in Children with Cancer in a Single Center in South India - Lashkari, Harsha Prasada; Prasada, Shobha; Joshi, Jayatheerth; Rao, Sadashiva (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction The overall cure rate of childhood cancers is above 79% in the developed world, whereas in the developing world, like in India, it is around 50%. It is vital to know the routes of presentation and factors affecting the presentation of childhood cancers in primary, secondary, and tertiary care to design a better survival strategy in childhood cancer.Objective The aim of this study was to know the factors affecting the time to diagnosis and time to treatment in children with cancers in a single center in South India.Materials and Methods It was a retrospective cohort study of children diagnosed with cancer between January 1, 2014 and December 31, 2016 at the pediatric oncology unit, KMC Hospital Mangalore, India. The patient interval, time to diagnosis, patient's family, economic background, parental education, and referral pattern were recorded, and its impact on the time taken to diagnosis was studied. The data was analyzed using SPSS 20.0 software.Results Out of 111 children, 72 were boys (64.8%). Fifty-one (46%) children belonged to the less than 5-year age group. The most common cancer was acute lymphoblastic leukemia, diagnosed in 50% (56/111) children, followed by acute myeloid leukemia in 14/111(12.6%), brain tumors in 9 (8.1%), and neuroblastoma in 10 (9%) children. The median patient interval/patient delay was 14 days (1–90 days), referral interval was 14 days (1–150 days), and overall time to diagnosis was 41 days (1–194 days). The first contact was the pediatrician in 86/111 (77.4%). Sixty-four percent (71/111) referral came from a secondary care hospital, and the remaining from the outpatient clinics. There was no difference in sex and patient interval (p = 0.278) and overall time to diagnosis (p = 0.4169), age (p = 0.041), mother’s education (p = 0.034), and type of cancer (p = 0.013) were three critical factors that determined the time to diagnosis.Conclusion Majority of the children diagnosed with cancer presented via referral from pediatricians. An equal number of them were referred to as routine and emergency patients. Age, mother's education, and type of cancers were the crucial factors associated with the overall time taken to diagnosis.
Keywords: childhood cancer; acute lymphoblastic leukemia; Time to diagnosis; diagnostic delay